Phase I study of ADI‐PEG20 plus low‐dose cytarabine for the treatment of acute myeloid leukemia. (30th March 2021) - Tsai, Hui‐Jen; Hsiao, Hui‐Hua; Hsu, Ya‐Ting; Liu, Yi‐Chang; Kao, Hsiao‐Wen; Liu, Ta‐Chih; Cho, Shih‐Feng; Feng, Xiaoxing; Johnston, Amanda; Bomalaski, John S.; Kuo, Ming‐Chung; Chen, Tsai‐Yun
Abstract: Most acute myeloid leukemia (AML) cells are argininosuccinate synthetase‐deficient. Pegylated arginine deiminase (ADI‐PEG20) monotherapy depletes circulating arginine, thereby selectively inducing tumor cell death. ADI‐PEG20 was shown to induce complete responses in 10% of relapsed/refractory or poor‐risk AML patients. We conducted a phase I, dose‐escalation study combining ADI‐PEG20 and low‐dose cytarabine (LDC) in AML patients. Patients received 20 mg LDC subcutaneously twice daily for 10 days every 28 days and ADI‐PEG20 at 18 or 36 mg/m 2 (dose levels 1 and 2) intramuscularly weekly. An expansion cohort for the maximal tolerated dose of ADI‐PEG20 was planned to further estimate the toxicity and preliminary response of this regimen. The primary endpoints were safety and tolerability. The secondary endpoints were time on treatment, overall survival (OS), overall response rate (ORR), and biomarkers (pharmacodynamics and immunogenicity detection). Twenty‐three patients were included in the study, and seventeen patients were in the expansion cohort (dose level 2). No patients developed dose‐limiting toxicities. The most common grade III/IV toxicities were thrombocytopenia (61%), anemia (52%), and neutropenia (30%). One had an allergic reaction to ADI‐PEG20. The ORR in 18 evaluable patients was 44.4%, with a median OS of 8.0 (4.5‐not reached) months. In seven treatment‐naïve patients, the ORR was 71.4% and the complete remission rate was 57.1%. The ADI‐PEG20 and LDC combination was well‐tolerated and resulted in an encouraging ORR. Further combination studies are warranted. (This trial was registered in ClinicalTrials.gov as a Ph1 Study of ADI‐PEG20 Plus Low‐Dose Cytarabine in Older Patients With AML, NCT02875093). Abstract : Combination of ADI‐PEG20 at 36 mg/m2 with LDC is tolerable with acceptable toxicities in relapsed/refractory or poor‐risk acute myeloid leukemia and induced an overall response rate of 44.4% and a median overall survival of 8.0 months, The overall response rate and complete remission rate are 71.4% and CR of 57.1%, respectively, in treatment‐naive patients. This regimen suggests the synergistic effect of the combination of ADI‐PEG20 and chemotherapy and is warranted for further study.